Improving the Value of Cull Cows by Feeding Prior to Slaughter - Jeffrey N. Carter; Dwain D. Johnson (EDIS)
AN169, a 5-page fact sheet by Jeffrey N. Carter and D. Dwain Johnson, demonstrates that income from cull cows can be increased when fed prior to slaughter. Describes the results of experiments of feeding cull cows in central Florida. Includes references. Published by the UF Department of Animal Science, August 2007.